Factors Determining Indonesian Muslim Behaviour in Purchasing Halal Food: A Preliminary Study - La Ode Alimusa; Adinda Septiani M; Ririn Tri Ratnasari; Hasan Aedy (ETIKONOMI, 2023)
Halal food and consumer behaviour are hot issues in scholarly publications. However, research exploring the factors determining consumer decisions by the exploratory study is still rare. Therefore, this study aimed to identify the factors that determine Indonesian Muslims' purchasing of halal food. We focused on halal food Muslim consumers and 140 questionnaires were distributed. Exploratory Factor Analysis and Confirmatory Factor Analysis was used for data analysis. The findings showed that three main factors determine Muslim purchase decisions for halal food: halal awareness, religiosity, and the safety & quality of halal food. A novel model of halal food consumer behaviour that implies the application of Halalan-tayyibah in Islamic teachings, namely the integration of halalness with product safety and quality. The study also implies that business players must pay attention to halal aspects in all business processes, from manufacturing to marketing, for the halal food value chain to be fully fulfilled.JEL Classification: M21, M31, Z12How to Cite:Alimusa, L.O., Septiani M, A., Ratnasari, R. T., & Hasan, A. (2023). Factors Determining Indonesian Muslim Behavior in Purchasing Halal Food: A Preliminary Study. Etikonomi, 22(2), 263 – 276. https://doi.org/10.15408/etk.v22i2.26979.